NEW GEOCHEMICAL PARAMETERS OF A QUANTITATIVE ASSESSMENT OF INTENSITY OF DEVELOPMENTS OF PROCESS OF HYDROMORPHIE TRANSFORMATION LOESS OF ROCKS - KORNIEIENKO, S.; SHNIUKOV, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of results received during performance of special complex researches of basic sites of development sink morpfosculptures in territory of region North West seaboard Black Sea Are the principles and parameters of a qualitative and quantitative estimation of a degree of loam and degradation of less adjournment in contours of structures are developed.